Measuring the organizational innovation impact towards the performance of SME’s in Malaysia - Abdul Wahab, Noor Akmal; Abdul Majid, Izaidin; Dora, Mohd Taib; Abdul Razak, Muhammad Hafiz (2012)
Under the The National Innovation Agenda there will be more SME development programmes that will focus on developing SME‟s to be more innovative, competitive and resilient. This research basically set out to examine the roles of organizational innovativess in predicting a small and medium firm‟s business performance. The objectives of this paper are to measure the impacts of organizational innovation towards the performance of Malaysian SME‟s and to identify the barriers holding back innovation. There are many results from previous studies supported the significance of organizational innovativeness with firm performance. The results of this research suggest that organizational innovativeness in an organization has a statistically significant positive impact on firm performance. The organizational innovativeness contributes and plays an important role in enhancing firm performance with both direct and indirect effects.